Adaptation and Construct Validity of the Organizational Commitment Questionnaire (OCQ) in Indonesian Student Organizations - Fadia Nada; Cut Ita Zahara; Dara Humayra Sahari; Ayunda Rizkiya; Dwi iramadhani; Riza musni; Rahmia Dewi (Jurnal Psikologi Terapan, 2025)
This study aimed to adapt and validate the Organizational Commitment Questionnaire (OCQ) for use among university students actively involved in student organizations in Indonesia. The adaptation process involved several stages, including pre-conditioning, expert judgment, and backward translation. The participants consisted of 240 Indonesian university students who were actively engaged in campus organizations. Data were analyzed using item validity testing, Cronbach’s Alpha reliability analysis, and Confirmatory Factor Analysis (CFA) to examine construct validity. The results indicated that out of the original 15 items, 6 items were found to be invalid and subsequently removed, resulting in a final model consisting of 9 items. The modified model demonstrated good fit with the empirical data, with a Cronbach’s Alpha coefficient of 0.931 and an Average Variance Extracted (AVE) value of 0.626, indicating high internal consistency and adequate convergent validity. Therefore, the adapted version of the OCQ can be considered a valid and reliable instrument for measuring organizational commitment among Indonesian university students involved in student organizations